Sex differences in acute cardiovascular care: a review and needs assessment. Issue 3 (5th March 2021) - Vallabhajosyula, Saraschandra; Verghese, Dhiran; Desai, Viral K; Sundaragiri, Pranathi R; Miller, Virginia M
Abstract: Despite significant progress in the care of patients suffering from cardiovascular disease, there remains a persistent sex disparity in the diagnosis, management, and outcomes of these patients. These sex disparities are seen across the spectrum of cardiovascular care, but, are especially pronounced in acute cardiovascular care. The spectrum of acute cardiovascular care encompasses critically ill or tenuous patients with cardiovascular conditions that require urgent or emergent decision-making and interventions. In this narrative review, the disparities in the clinical course, management, and outcomes of six commonly encountered acute cardiovascular conditions, some with a known sex-predilection will be discussed within the basis of underlying sex differences in physiology, anatomy, and pharmacology with the goal of identifying areas where improvement in clinical approaches are needed.